Alterações metabólicas e morfométricas induzidas por hipóxia em Gallus gallus - Toro Velasquez, Paula Andrea [UNESP] (2014)
Low O2 partial pressure during embryonic and fetal development can decrease the growth and metabolic rate of the embryo, leading to morphophysiological changes after birth, and blunt the hypoxic ventilatory response in newly hatched chicken. In the present study, different conditions during incubation (cold and hypoxia) were performed to evaluate the effect of prenatal hypoxia on metabolic rate, and the response to acute hypoxia in different strains and ages of Gallus gallus. We also considered the possibility that prolonged metabolic depression per se, but not specifically induced by hypoxia, during incubation would be a contributing factor to decreased metabolic rate in neonate. Thus chicken embryos were incubated at 35◦C (cold group), which is known to decrease the embryonic oxygen consumption (VO2) by ~ 30% throughout the incubation period and increases the incubation time in ~2 days. Finally, in precocial birds, no study has approached the influence of hypoxia at different stages of incubation in the morphometric development of the intestine, not only important for the digestive processes and absorption, but also for protection against pathogens, so we evaluated the morphometric characteristics and quantity of goblet cells per villi of the small intestine regions in newly hatched broiler chicks